MicroRNA‐3178 ameliorates inflammation and gastric carcinogenesis promoted by Helicobacter pylori new toxin, Tip‐α, by targeting TRAF3. Issue 2 (5th August 2016) - Zou, Meijuan; Wang, Fang; Jiang, Aiqin; Xia, Anliang; Kong, Siya; Gong, Chun; Zhu, Mingxia; Zhou, Xin; Zhu, Jun; Zhu, Wei; Cheng, Wenfang
Abstract: Background: Helicobacter pylori infection is the main cause of chronic gastritis, peptic ulcer, and gastric cancer. Tip‐ α is a newly identified carcinogenic factor present in H. pylori . TRAF3 can activate NF‐κB by both canonical and noncanonical signaling pathways. In this study, we found that the expression of TRAF3 and NF‐κB was upregulated, while microRNA‐3178 (miR‐3178) was decreased in H. pylori ‐positive gastric tissues but not in H. pylori ‐negative tissues. Materials and Methods: GES‐1 cells were incubated with 12.5 μg/mL recombinant Tip‐α (rTip‐α) in RPMI1640 for 2 hours. After another 24 hours, the supernatant medium was designed as inflammatory‐conditioned medium (ICM) and that from the untreated control cells was designed as untreated control medium. The release of proinflammatory cytokines from GES‐1 cells and proliferation of gastric cancer cells was determined by ELISA and CCK‐8 kits. Cells were transfected with the mimic, inhibitor, negative control of miR‐3178, or TRAF3 siRNA control siRNA. The medium was then replaced with RPMI1640, 12.5 μg/mL rTip‐α, and collected, and the total cellular RNA and protein were extracted for the following detection. Results: MiR‐3178 mimic prevented the increasement of TRAF3 and hence decreased activation of NF‐κB signals, whereas miR‐3178 inhibitor could not, in GES‐1 cells with Tip‐α treatment. The condition medium from miR‐3178 mimic transfected GES‐1 cells could inhibit proliferation and induce apoptosis of inflammation‐related gastric cancer cells SGC7901 and MGC803 by decreasing the production of inflammatory cytokines TNF‐α and IL‐6, which were secreted by GES‐1 cells. Conclusions: Taken all together, Tip‐α might activate NF‐κB to promote inflammation and carcinogenesis by inhibiting miR‐3178 expression, which directly targeting TRAF3, during H. pylori infection in gastric mucosal epithelial cells.